The Petra Church revisited. 1992-2011 - PORTER, Barbara (ACOR Newsletter, 2011)
This article offers a detailed and informative description of current efforts to restore mosaics of both opus sectile and opus tessellatum in the church, which was badly damaged by a fire ca. 600 C.E., causing considerable damage to the mosaic pavements and also carbonizing a papyrus archive. An excellent ground plan locates all of the pavements in the church. This is a second campaign of mosaic conservation following an earlier one in 1992-1993 conducted by T. Roby. Recent restoration of the opus sectile floors was undertaken by E. Di Carlo and C. Tedeschi, based on graphic evidence provided by P. Bikai. In addition, F. Sciorilli (who worked closely with M. Piccirillo at Mt. Nebo) and A. Vaccalluzzo were able to stabilize several tessellated pavements, which had deteriorated in the previous decade. Attention focused on the church’s south aisle, including a mosaic of the Seasons found there. Pavement sections were initially cleaned on the surface and then lifted and placed on a new mortar bed, before being reset in their original location. The process revealed the ancient mosaic foundations, including a mortar bed with a mixture of ash, charcoal, and lime plus discarded tesserae; a sandy layer below; and finally a foundation of medium-sized pebbles. The Petra Church Conservation Endowment helped finance the restoration work. There is a persistent problem of inadequate water drainage.
p. 1-5, ill. coul.
Keywords: Bibliographie par pays, région ou ensemble géographique; Analyse physico-chimique; Église (Petra, JOR); Restauration; Destruction de mosaïque; Dépose de mosaïque; Restaurateur; Analyse pétrographique; Incendie; Drainage; Support de mosaïque; Opus sectile; Saison (personnification, symbole); Mont Nebo; Petra